Strategi Konsep Bukaan Untuk View Outdoor Dan Pencahayaan Alami Pada Perancangan Interior Ruang Rawat Inap Rumah Sakit - Simarmata, Andriano (ATRAT: Jurnal Seni Rupa, 2024)
The hospital inpatient room is a service facility for the patient in their healing process. Inpatient facilities have standardized operational procedures based on national regulations, which sometimes becomes a limitation in developing designs because they must refer to functional suitability. This writing aims to provide a strategy formulation and concept of openings as access to outdoor views and natural lighting in hospital inpatient rooms to optimize the principles of the healing environment. This article was carried out by reviewing design standards for hospital inpatient rooms based on guidelines and regulations issued by the Indonesian Ministry of Health and previous research. The research was carried out by experimenting with the orientation of the facade openings from (East, South and Southeast) to assess the optimal daylighting in the interior. A more in-depth discussion of design strategies and technical implementation in interior design will be discussed..